Heat: An Overlooked Tool in the Practicing Hydrogeologist's Toolbox. Issue 4 (20th June 2019) - Kurylyk, Barret L.; Irvine, Dylan J.
Abstract : Article Impact Statement : Groundwater researchers and practitioners should include temperature in the suite of standard measurements and analyses.